Vitiligo-like lesions following imatinib mesylate therapy: a case series and review of literature - Neerja Saraswat; Shekhar Neema; Sushil Kumar (Pigment International)
Imatinib mesylate (IM), a tyrosine kinase inhibitor, has become a standard of care for the management of chronic myeloid leukemia. The safety profile of IM is favorable; however, few adverse effects such as gastrointestinal disturbances, fluid retention, skin rashes, and myelosuppression have been reported. Hypopigmentation of the skin is a rare adverse effect of IM. In this report, we describe two cases of chronic myeloid leukemia who developed skin hypopigmentation while on IM.